Management of obsessive-compulsive disorder with fluvoxamine extended release - Lídia Ordacgi (Dove Medical Press, 2009)
Lídia Ordacgi1, Mauro V Mendlowicz2, Leonardo F Fontenelle11Anxiety and Depression Research Program, Institute of Psychiatry, Universidade Federal do Rio de Janeiro (IPUB/UFRJ), Rio de Janeiro, Brazil; 2Department of Psychiatry and Mental Health, Universidade Federal Fluminense (MSM-UFF), Niterói, BrazilAbstract: The pharmacodynamic properties of fluvoxamine maleate include the modulation of different populations of serotonergic, dopaminergic, and sigma receptors and/or transporters, a complex pattern of activity that may account for its efficacy in the treatment of obsessive-compulsive disorder (OCD). Nevertheless, its pharmacokinetic profile and its pattern of side effects may hinder a rapid dose escalation, a therapeutic strategy that might be utterly desirable in patients with OCD. In preclinical studies, the maximum plasma concentration and bioavailability of an extended-release (CR) formulation of fluvoxamine were, respectively, 38% and 16% lower than those of the standard (ie, non-CR) formulation. Recently, the US Food and Drug Administration approved the fluvoxamine CR formulation for the treatment of OCD in adults. This approval was based on the results of a double-blind, placebo-controlled study with 253 OCD patients in which fluvoxamine CR showed a consistently earlier onset of therapeutic effects than other selective serotonin reuptake inhibitors, as reported in previous studies. The use of the CR formulation of fluvoxamine allowed a particularly aggressive dosing strategy at the beginning of the titration phase, ie, treatment could be started with a single dose of fluvoxamine CR 100 mg at bedtime, while keeping the occurrence of side effects and the rate of compliance at levels comparable to those reported for the use of immediate-release fluvoxamine.Keywords: obsessive-compulsive disorder, fluvoxamine, fluvoxamine extended release